Economic literacy and inflation expectations: Evidence from a laboratory experiment - Mary A. Burke; Michael Manz (Federal Reserve Bank of Boston, 2011)
We present new experimental evidence on heterogeneity in the formation of inflation expectations and relate the variation to economic literacy and demographics. The experimental design allows us to investigate two channels through which expectations-formation may vary across individuals: (1) the choice of information and (2) the use of given information. Subjects who are more economically literate perform better along both dimensions - they choose more-relevant information and make better use of given information. Compared with survey data on inflation expectations, fewer demographic factors are associated with variation in inflation expectations, and economic literacy in most cases accounts for demographic variation in expectations.
Keywords: E31; E37; E52; 330